LEGAL CERTAINTY ON ASTRA CHILDREN'S INHERITANCE RIGHTS FOR RECOGNITION OF BIOLOGICAL CHILDREN BASED ON STATE COURT DECISIONS: KEPASTIAN HUKUM HAK MEWARIS ANAK ASTRA ATAS PENGAKUAN ANAK BIOLOGIS BERDASARKAN PUTUSAN PENGADILAN NEGERI - ni putu yuliana kemalasari (VYAVAHARA DUTA, 2023)
A child cannot choose where and when they are born, therefore there are often instances where a child is born in a situation that is deemed illegitimate according to the law, namely a child born out of wedlock. The Marriage Law stipulates that a valid marriage is one conducted between a man and a woman based on their respective religious beliefs and convictions, recorded according to the provisions of applicable regulations. In the context of Balinese customary law, there exists a term known as “anak astra” for a child born out of wedlock whose father belongs to a higher caste than the mother. The presence of “anak astra” leads to discrimination against the rights of such children. In society, “anak astra” cannot have the same rights as their legitimate siblings, even if their parents later formalize their marriage, including inheritance rights. To address this issue, a normative juridical research method with literature study is employed. Therefore, an effort to legitimize “anak astra” can be achieved by recognizing and confirming them as legitimate children through a court declaration, subsequently recorded in the child’s birth certificate. In civil law, a child born out of wedlock who has been legitimized by a court decree changes their status to that of a legitimate child and obtains their rightful legal entitlements, but this is not the case in Balinese customary law, which does not equate the rights of “anak astra” with those born from valid marriages. Keywords: child out of wedlock, Balinese Customary Inheritance Law, Determination of Biological Children